The transmission routes of African swine fever during an outbreak in Serbia July–August 2023: African swine fever virus detections in environmental samples and insects - Vasić, Ana; Milovanović, Bojan; Glišić, Dimitrije; Kavran, Mihaela; Kureljušić, Jasna; Živulj, Aleksandar; Kureljušić, Branislav; Milićević, Vesna (Frontiers in Veterinary Science, 2024)
African swine fever (ASF) is a highly contagious viral disease of domestic pigs and wild boar (Sus scrofa) caused by an arbovirus- African swine fever virus (ASFV), which is classified into the family Asfarviridae. Even though the main transmission route of ASFV is direct contact between animals and carcasses releasing ASFV into the environment, the role of other transmission routes such as via environmental contamination or insects remains in great part unclear. During an epidemic f ASF in Serbia in 2023, environmental samples (soil, feed, water and swabs from the pig barns), and insects [resulting in collection of adult and/or larval stages of non-biting flies (Diptera: Calliphoridae and Muscidae)] were collected in four locations in South Banat district of Serbia. To assess the possibility that insects carry the ASFV in infected courtyards, sticky fly traps and open Petri dishes containing meat mixed with humid cotton wads were offered in three locations during the five days of the experiment in the Belgrade area. Furthermore, to confirm the role of flies in ASF in mechanical transmission pathway in Serbia, L2 and L3 larvae of flies (Lucilia sericata Meigan, 1826; Stomoxys calcitrans Linnaeus, 1758) were collected from the pig carcasses from infected farms, bred to adults in the Laboratory and an ASFV spiked meat meal was placed into cages with three-day-old flies (n = 52) to estimate positivity of flies and duration of mechanical transmission of ASFV. The results from the environmental samples showed no positive ASFV DNA detection, the same was true for the samples from meat-based traps and sticky fly traps, while ASFV DNA was detected in three samples containing eggs, L1 and L3 fly larvae collected from carcasses and adult flies (L. sericata). In experimental conditions, only one S. calcitrans fly tested positive on day 1 post-infection. The results implicate the possible role of Lucilia sp. flies in the mechanical transmission of ASFV as well as S. calcitrans in Serbia during an outbreak, while ASFV DNA was not detected in environmental samples in this study.